Thermodynamic properties of binary mixtures containing of hydrofluorocarbons and hydrofluorolefins: new data and modelling - Tsuji, Tomoya (2018)
Hydrofluorolefins (HFOs) are a new class of more environmentally-friendly refrigerant with zero ozone depletion potential, low global warming potentials, and low flammability. In this work, thermophysical property data for equimolar mixtures of HFOs (specifically R1234yf and R1234ze(E)) and hydrofluorocarbons (R32, R125, R134a, R143a, and R152a) are presented. Our measurements were combined with literature data available for these binary mixtures to optimize the mixture parameters in the models used in NIST REPFROP 9.1 and thereby improve thermodynamic property predictions for mixtures of HFO and HFC refrigerants. Significant improvements in the predicted properties were achieved, particularly for the density where, for the example of (R143a + R1234yf), the deviation of the model from the data was reduced from over 1 % to 0.06 %. The measurements and modelling conducted in this work should allow the more accurate simulation of refrigeration processes using mixtures of these refrigerants.